PEMBERIAN PENGETAHUAN MENGENAI EKONOMI POLITIK KEPADA REKAN-REKAN ALUMNI - Posma Sariguna Johnson Kennedy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
In this era of information disclosure, the campaign to win a candidate is carried out in various ways. The purpose of this Community Service is to conduct socialization so that recipients of information will not be trapped in a heated situation with lots of hoaxes and misleading information. This activity was carried out using the focus group discussion method through the online